Impacto del VIH/sida en las dimensiones del cuestionario de calidad de vida de la OMS y sus factores determinantes (2013)
ABSTRACT : Introduction: Quality of Life of people living with HIV/AIDS in Medellín has not been evaluated with specific instruments. Objective: To describe the impact of HIV/AIDS in the dimensions of the WHOQOL-HIV BREF in people living with HIV/AIDS in Medellin, Colombia, 2010-2011, and its association with determinants factors. Methods: Cross sectional study in adults with HIV/AIDS in Medellín. We used primary source of information that included a survey with demographic, socioeconomic and clinical aspects, SMAQ and WHOQOL-HIV BREF. The analysis was based on frequency and summary measures, parametric and nonparametric tests, and linear regression. Results: In all dimensions of quality of life the score was equal to or greater than 60, the lowest score was observed in the physical health and greater independence. The main determinants of quality of life were economic satisfaction, family relationships, education, comorbidities and social stratum. Conclusion: Due to the increasing prevalence of HIV/AIDS, the effectiveness of antiretroviral therapy, its chronic nature, the possibility of treatment and survival, quality of life is a key factor for those living with the infection.